OP0244 High Expression of Prostaglandin E2 in Zygapophyseal Joints of Patients with Ankylosing Spondylitis and Osteoarthritis. (23rd January 2014) - Bleil, J.; Appel, H.; Maier, R.; Sieper, J.; Syrbe, U.
Abstract : Background: A study by Poddubnyy et al. showed that a high NSAIDs intake over 2 years is associated with retarded radiographic spinal progression in AS [1 ] suggesting that NSAIDs might prevent new bone formation in patients with ankylosing spondylitis (AS). Objectives: In order to determine prostaglandin E2 (PGE2 ) expression at sites of bone remodeling we performed an immunohistochemical study analyzing PGE2 expressing cells in zygapophyseal joints of AS patients in comparison to autopsy controls and patients with osteoarthritis (OA). Methods: PGE2 was determined in zygapophyseal joints from 13 AS, 11 OA patients and 10 controls (autopsies without spinal diseases). Immunohistochemistry was performed to detect PGE2 + cells per total cell number at four different sites: within hyaline cartilage, subchondral bone plate, trabecular bone and fibrous tissue replacing subchondral bone marrow. Results: About 50 percent of the chondrocytes expressed prostaglandin E2 in autopsy controls. While PGE2 expression in chondrocytes of OA patients was significantly increased compared to controls (p=0.0015), a trend towards increased numbers of PGE2 + chondrocytes was also found in AS patients (p=0.1095). For osteocytes within the subchondral bone plate and the trabecular bone a similar trend was seen: more osteocytes were PGE2 positive in joints of AS patients (41.80±16.42%; 41.16±21.15%) and OA patients (44.82±15.47%; 49.25±16.32%) patients than in controls (20.33±16.69%; 32.18±18.88%). Fibrous tissue, replacing the subchondral bone marrow and invading the subchondral bone plate, is a typical feature of AS and OA joints, but not seen in controls. Here we found that more than 80 percent of the cells expressed PGE2 (AS 84.82±9.00%; OA 87.88±13.38%), without differences between AS and OA patients (p=0.1902). Conclusions: PGE2 is highly expressed within zygapophyseal joints, including the cells of cartilagineous and bony regions. However also within the fibrous tissue high expression rates were detected suggesting that PGE2 is expressed by many cell types within joints which could be potentially targeted by a NSAID therapy. In spite of the knowledge that NSAIDs are highly effective in reduction of symptoms such as pain and therefore represent a first-line therapy in AS and OA [2, 3 ], further studies are required to determine the impact of PGE2 on the function and differentiation of cells potentially involved in aberrant new bone formation in AS and OA. References: Poddubnyy D, Rudwaleit M, Haibel H, Listing J, Marker-Hermann E, Zeidler H, et al. Effect of non-steroidal anti-inflammatory drugs on radiographic spinal progression in patients with axial spondyloarthritis: results from the German Spondyloarthritis Inception Cohort. Annals of the rheumatic diseases. 2012 Oct; 71(10):1616-1622. Poddubnyy D, van der Heijde D. Therapeutic controversies in spondyloarthritis: nonsteroidal anti-inflammatory drugs. Rheumatic diseases clinics of North America. 2012 Aug; 38(3):601-611. Stam W, Jansen J, Taylor S. Efficacy of etoricoxib, celecoxib, lumiracoxib, non-selective NSAIDs, and acetaminophen in osteoarthritis: a mixed treatment comparison. The open rheumatology journal. 2012; 6:6-20. Disclosure of Interest: None Declared